PPARγ/ETV2 axis regulates endothelial‐to‐mesenchymal transition in pulmonary hypertension - Dong Hun Lee; Minseong Kim; Sarah S. Chang; Raham Lee; Andrew J. Jang; Juyoung Kim; Jing Ma; Michael J. Passineau; Raymond L. Benza; Harry Karmouty‐Quintana; Wilbur A. Lam; Benjamin T. Kopp; et al. (Pulmonary Circulation)
Abstract Endothelial‐to‐mesenchymal transition (EndoMT) plays an important role in pulmonary hypertension (PH) but the molecular mechanisms regulating EndoMT remain to be defined. We demonstrate that the axis of the transcription factors PPARγ (Peroxisome Proliferator‐Activated Receptor gamma) and ETV2 (ETS variant 2) play important roles in the pathogenesis of PH. Decreased levels of the expression of PPARγ and ETV2 along with reduced endothelial and increased EndoMT markers are consistently observed in lungs and pulmonary artery endothelial cells (PAECs) of idiopathic pulmonary arterial hypertension patients, in hypoxia‐exposed mouse lungs, human PAECs, and in induced‐EndoMT cells. Etv2+/− mice spontaneously developed PH and right ventricular hypertrophy (RVH), associated with increased EndoMT markers and decreased EC markers. Interestingly, chronic hypoxia exacerbated right ventricular systolic pressure and RVH in Etv2+/− mice. PPARγ transcriptionally activates the ETV2 promoter. Consistently, while mice overexpressing endothelial PPARγ increases the expression of ETV2 and endothelial markers with reduced EndoMT markers, endothelial PPARγ KO mice show decreased ETV2 expression and enhanced EndoMT markers. Inducible overexpression of ETV2 under induced‐EndoMT cell model reduces number of cells with mesenchymal morphology and decreases expression of mesenchymal markers with increased EC makers, compared to control. Therefore, our study suggests that PPARγ‐ETV2 signaling regulates PH pathogenesis through EndoMT.